2017
DOI: 10.1093/ons/opx106
|View full text |Cite
|
Sign up to set email alerts
|

sEEG is a Safe Procedure for a Comprehensive Anatomic Exploration of the Insula: A Retrospective Study of 108 Procedures Representing 254 Transopercular Insular Electrodes

Abstract: In the presurgical evaluation of drug-resistant epilepsy, the insular cortex can be explored safely and comprehensively using transopercular sEEG electrodes. Parasagittal oblique trajectories may also be associated to achieve an optimal exploration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 31 publications
1
35
0
Order By: Relevance
“…The patient was stereotactically implanted with three multicontact intracerebral electrodes targeting the right ventral OT cortex, according to a well‐defined and previously described procedure (Jonas et al, ; Salado et al, ). Each intracerebral electrode consisted of a cylinder of 0.8 mm diameter and contained 8–11 independent recording contacts of 2 mm in length separated by 1.5 mm from edge to edge and by 3.5 mm center to center.…”
Section: Methodsmentioning
confidence: 99%
“…The patient was stereotactically implanted with three multicontact intracerebral electrodes targeting the right ventral OT cortex, according to a well‐defined and previously described procedure (Jonas et al, ; Salado et al, ). Each intracerebral electrode consisted of a cylinder of 0.8 mm diameter and contained 8–11 independent recording contacts of 2 mm in length separated by 1.5 mm from edge to edge and by 3.5 mm center to center.…”
Section: Methodsmentioning
confidence: 99%
“…There were 12 studies 15-26 that reported on epilepsy duration, with no significant difference between SEEG patients (mean = 126.8 months ± 65.0, median = 121.8) and SDE patients (mean = 62.4 months ± 51.1, median = 51.4; Table 2). Among the SEEG patients, the etiology was identified as a temporal epileptogenic focus in 42.2% of patients, 15,22,23,[26][27][28][29] tumor in 6.7% of patients, 22,23,27,28,30 FCD1 in 39.2% of patients, 16,23,27,28,[31][32][33] FCD2 in 10.7% of patients, 23,28,31 and lesional in 41.5% of patients. [15][16][17]22,23,[28][29][30][31]34 Among the SDE patients, the etiology was identified as a temporal epileptogenic focus in 40.9% of patients, 18,21,25,[35][36][37][38][39][40][41][42][43][44][45...…”
Section: Cohort Descriptionmentioning
confidence: 99%
“…Increasing interest in insular epilepsy has emerged during the past decade from studies based on stereo-electroencephalography (SEEG) methodology. [1][2][3][4][5][6][7] SEEG techniques for implanting the insula safely have been developed, [8][9][10][11][12][13] and there is growing evidence that SEEG is particularly effective in demonstrating insular seizure onset. [14][15][16] However, the insula lies deep in the sylvian fissure, covered by eloquent frontal, temporal, and parietal opercula with a dense network of vessels.…”
Section: Introductionmentioning
confidence: 99%